DESAIN ONE-CARD SYSTEM BERORIENTASI OPERASI PROSES PELAYANAN AKADEMIK (Studi Kasus di Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman Purwokerto) - Dimastuti Dimastuti; Bambang Sunarko; Jaryono Jaryono (Universitas Peradaban, 2014)
Faculty of Economics and Business of Jenderal Soedirman University Purwokerto is a formal education that can’t be separated from technological development. But in fact, the Faculty is still using manual facilities in the academic services of the operating system so it means that situation still not efficient and effective for students and College as well. To solve the problem, RFID is appropriate technology. Students and staff will have only one RFID card as an identity card and they can use the cards for various purposes such as loaning books, parking a vehicle and present students list. It provides system that easy, comfortable, effective, and efficient.The results of this research will show the model of design one-card system using RFID technology (Radio Frequency Identification) that will be applied in the process of academic services at the Faculty of Economics and Business of Jenderal Soedirman University Purwokerto.